The potential use of Rattus norvegicus (Mammalia, Muridae) in experimental infections with metacercariae of Paragonimus mexicanus (Digenea, Troglotematidae) - Hernández Chea, Roderico (2017)
Seven Wistar rats (Rattus norvegicus) were experimentally infected with Paragonimus mexicanus metacercariae, obtained from organs and tissues of freshwater crabs (Brachyura: Pseudothelphusidae) collected from the Caribbean of Costa Rica. Four rodents were infected orally and three by intraperitoneal injection. Eggs of P. mexicanus were found in a stool sample five months post-infection in one of the rodents infected intraperitoneally. Five out of seven rats, developed worms, three inmature, and two adult ones. Worms obtained from rats infected intraperitoneally showed development of gonads with presence of eggs in the uterus. Although the recovery rate of worms was low (media: 2.3%), the susceptibility of these rodents to this trematode species was demonstrated as mature adults of P. mexicanus were obtained from Wistar rats. The use of Wistar rats as an animal model for experimental infections in further investigations is recommended.